Academic Hope Among Special Education Students (Journal of the College of Basic Education, 2026)
University students are an important segment of society. They are more hopeful. Their sense of personal and social superiority has made them compatible in their lives, and they feel highly hopeful. They possess awareness and knowledge of their lives, and they are able to achieve their desires and ambitions according to their abilities to face life's events. One of the problems that has attracted the attention of researchers is that hope is linked to many psychological processes and outcomes related to physical and mental health. Studies have shown that a lack of hope leads to negative effects, including depression and suicidal behavior. Low hope also contributes to a sense of learned helplessness, pessimism, negative emotions, impaired learning ability, and a negative evaluation of events.People with low levels of hope suffer from a lack of means to help them achieve their ambitions. They doubt their abilities and choose goals that are either too simple or too difficult. They believe their chances of achieving what they desire are slim. They feel hesitant and fearful of failure, and experience negative emotions while striving to achieve their desires. The study showed that individuals with low hope typically do not benefit from their experiences to improve their future performance. On the contrary, they feel hopeless and frustrated because their self-confidence is unstable. This increases their anxiety and failure, leading them to develop negative personalities that are incompatible with society. The research is of great importance, as university students are an important segment of society. They are more hopeful. Their sense of personal and social superiority has made them compatible in their lives, and they feel highly hopeful. They possess awareness and knowledge of their lives, and they are able to achieve their desires and ambitions according to their abilities to face life's events. Snyder believes that university students are among the conscious segments that possess academic hope and optimism about their future. They possess high levels of thinking, which is reflected in their awareness and expectations of continued success in their academic and professional lives (Snyder 2002, p. 503). The research is limited to students at Al-Mustansiriya University, College of Basic Education, for the academic year (2022-2023), in the humanities and sciences, and for both genders.